COMMUNICATION AND IDENTITIES OF DEAF - Grujić, Nikola M (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
Communication and language are one of the central elements of every culture. Taking as an example persons who cannot hear we can see how a language becomes not only the foundation of culture, but also a strong identity qualifier. Probably the most precise definition of Deaf culture would be a social and creative power of the community standing on sign language. This paper seeks for answers to the questions such as how deaf people manage in the imposed mainstream communication, what do ’oralist’ recommend and why is visualization of communication much more important and natural for the Deaf than ’imitation’ and/or correction? The article attempts to encourage broader academic and social discussion on topics such as fundamental rights, social inclusion and culture (subculture) of the Deaf, incursion into or respect for autonomy of the values lived and promoted by the Deaf society, education of deaf children and youth, development of international sign language, self presentation and self representation of the community of non-hearing...Full recognition of national sign languages shall go in line with effective implementation of national policies for inclusive education, respecting the cultural specifics of the community of Deaf. Functional translation services together with other support services are basic requests of the Deaf so that the minimum of their rights is respected and the path towards equality is made. At the same time, the Deaf themselves should be more ’vocal’ when requesting equal accessibility to goods and services as well as the equality for all persons with disabilities.